Reintervention after abdominal aortic aneurysm repair - who is to blame? - Jácome,Filipa (2022)
Abstract Introduction: Endovascular repair of abdominal aortic aneurysm (EVAR) is often recommended as first option for patients with suitable abdominal aortic aneurysm (AAA) anatomy. Nevertheless, this treatment carries higher reintervention rates and possibly higher aneurysm and all cause-related mortality in the long run versus open surgery. This narrative review aims to convey recent data about surveillance and the frequency and indications for reintervention after EVAR. Methods: A comprehensive narrative review was conducted, providing a critical and objective analysis of the current knowledge on a topic. Results: EVAR-1 trial reported lower total and aneurysm-related mortality in the first 6 months after EVAR patients, with increasing follow-up time the mortality rate increased, leading to a higher total and aneurysm-related mortality, comparing with the open surgical repair group. There is no consensus on EVAR surveillance, and in the 15-year follow-up of EVAR-1 trial they found that EVAR is associated with a reintervention rate of up to 20% in the first 4 years. There is a press in need for a homogeneity and contemporary appraisal of surveillance after EVAR and in indications for reintervention. In order to accomplish that, it is of paramount importance that centers undergoing EVAR programs publish their results about the compliance of follow up after EVAR and reintervention rates Conclusion: Long term outcomes are the Achilles heel of the endovascular AAA repair. Adequate follow up and reintervention are of paramount importance for EVAR to achieve its full potential.